2010
DOI: 10.1021/ja107444m
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Threading Polythiophene: Defect-Free Insulated Molecular Wires Endowed with Long Effective Conjugation Length

Abstract: Herein, we report on a self-threading polythiophene whose conjugated molecular wire is sheathed within its own cyclic side chains. The defect-free insulating layer prevents electronic cross-communication between the adjacent polythiophene backbone even in the solid film. Notably, the covalently linked cyclic side chains extend the effective conjugation length of the interior polythiophene backbone, which results in an excellent intrawire hole mobility of 0.9 cm(2) V(-1) s(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
123
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 28 publications
6
123
1
Order By: Relevance
“…As reported previously, the bithiophene backbone in 3 is planarized owing to the strapped structure, 5 while that in 4 is known to be twisted. 9 Because of the difference in planarity, 3 and 4 should have distinct electronic structures.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…As reported previously, the bithiophene backbone in 3 is planarized owing to the strapped structure, 5 while that in 4 is known to be twisted. 9 Because of the difference in planarity, 3 and 4 should have distinct electronic structures.…”
supporting
confidence: 63%
“…8 If the monomer 4 was randomly incorporated into the poly-3 backbone, then the effective conjugation of the poly-3 backbone should be significantly reduced; for example, in the case of poly-3 8 4 2 , the poly-3 backbone could be stochastically segmented into conjugation as small as a tetramer or pentamer. 5 Nonetheless, the ππ* transition of the poly-3 backbone at 500600 nm was scarcely affected by 4, thus corroborating the block copolymer structure. Importantly, the spectra could be deconvolved into those of poly-3 and poly-4, which is consistent with the compositions of each block determined by 1 H NMR spectroscopy.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…33 A previous study by our group, conceptually related to the present study, has demonstrated that the dihedral angle of bithiophene is affected by cyclic side chains. [34][35][36][37] In STBm/n (Scheme 2), the movable range of the dihedral angle of the bithiophene backbone was defined by the length of the strap. The longer the strap, the larger the fluctuation of the dihedral angle (Scheme 2c).…”
Section: Synthesis Of Monomersmentioning
confidence: 99%